Optimization of lipid content in microalgae biomass using diluted palm oil mill effluent by varying nutrient ration - Aziz N.A.A.; Chelliapan S.; Ponraj M.; Yusof M.B.M.; Md Din M.F. (CRC Press, 2023)
Biomass; Cultivation; Economics; Effluents; Petroleum industry; Petroleum prospecting; Wastewater treatment; Economic growths; Environmental pollutions; Feasible solution; Microalgal cultures; Oil extraction; Oil industries; Oil palm plantations; Palm oil mill effluents; Palm oil